PENGARUH ZAT PENGATUR TUMBUH TERHADAP PERKECAMBAHAN BENIH DAN PERTUMBUHAN BIBIT KAMANDRAH (CROTON TIGLIUM L.) - Tjokrowardojo, Agus Sudiman; Rosman, Rosihan; Iswantini, Dyah (JURNAL AGROTROPIKA, 2009)
Study of growth regulator of kamandrah (Croton tiglium L.) by pot experiment was conducted in green house at Indonesian of Medicinal and Aromatic Crops Research Institute (IMACRI) Bogor. The experiment was conducted from Juni to Oktober 2008. In pot experiment to test the germination by treatments: a) Nitroaromatic at 0.5 ppm concentration, b) Nitroaromatic at 1.0 ppm concentration, c) Auxin + Cytokinine at 2.5 ppm concentration, d) Auxin + Cytokinine at 2.75 ppm concentration, e) Root Up at 0.5 ppm concentration, f) Root Up at 0.75 ppm concentration and g) control (without treatment). The assasment on 30 days after sowing (DAS), showed that treatments by Nitroaromatic at 0.5 dan 1.0 ppm, Auksin+ Citokinine at 2.5 dan 2.75 ppm were improved seed germination of kamandrah from 26.67% (by control) to 40.00 - 46.67 %. Nitroaromatic, Auxin + Cytokinine and IBA + NAA to improve seeds germination of kamandrah about 24 ? 74 % than control in 30 DAS. Seedlings growth of kamandrah by Nitroaromatic at 0.5 and 1.0 ppm, Auxine + Cytokinine at 2.5 and 2.75 ppm, IBA + NAA at 0.5 and 1.0 ppm were 11.15 ? 16.40 cm more higher than control (8.85cm). The number of branch treatments by Auxin + Cytokinine at 0.5 ppm (21.35/crop), Nitroaromatic at 0.5 and 1.0 ppm (19.35 and 17.15/crop), IBA + NAA at 0.5 ppm (17.15/crop) and Auxine at 2.75 ppm (16.75/crop) more than control significantly (14.45/crop). The assasment on 60 DAS showed that seedlings growth of kamandrah improved by plant growth regulators ie. Nitroaromatic, Auxin + Cytokinine and IBA + NAA.Key words: Plant growth regulator, seed germination, seedling, kamandrah (Croton tiglium L.).